Strong adhesion of hydrogels by polyelectrolyte adhesives. (7th October 2020) - Zhang, Jia-Nan; Zhu, Hengwei; Liu, Tianqi; Chen, Yuanyuan; Jiao, Chen; He, Changcheng; Wang, Huiliang
Abstract: The adhesion of hydrogels has drawn rapidly growing attention due to its wide potential applications. However, currently reported hydrogel adhesion methods are mostly complex and usually with low adhesion strength. Here we report a convenient and versatile method to achieve strong adhesion of hydrogels. By using negatively charged polyacrylic acid (PAA) and positively charged polyethyleneimine (PEI) as adhesives, strong adhesion is formed between the two hydrogels mainly through electrostatic interactions. Moreover, the adhesion energy can be further enhanced by the pre-complexation of PAA with Fe 3+ at a proper pH (3.0). It's worth noting that the highest adhesion energy of 2178 J/m 2 can be obtained after 10 days' setting. Additionally, the adhesion method enables multiple repeatable adhesion of hydrogels with 87% highly adhesion efficiency after three peeling off-rejoining cycles. This adhesion method can also be applied to the adhesion of other types of hydrogels and adhering hydrogels to other solid materials. Graphical abstract: Image 1 Highlights: Strong adhesion of hydrogels is achieved by using oppositely charged polyelectrolytes as adhesives. The highest adhesion energy is up to 2178 J/m 2 . Repeatable adhesion with a high adhesion efficiency up to 87% after three cycles is achieved. The method enables strong adhesion between hydrogels and solid substrates as well as biological tissues.